PENGARUH KUALITAS PELAYANAN TENAGA ADMINISTRASI RUMAH SAKIT TERHADAP KEPUASAN PASIEN DI UNIT INSTALASI RAWAT JALAN RUMAH SAKIT UMUM DAERAH ARIFIN ACHMAD PROVINSI RIAU - Wiwik Suryandartiwi; Meidita Tifani; Agus Salim (LPPM Universitas Awal Bros, 2022)
The quality of health services is a level that shows the perfection of health services, which can create a sense of satisfaction in every patient who gets benefits at the Arifin Achmad Hospital, Riau Province. Happiness will be fulfilled if the better the quality of service, the more satisfied the patient will be and will continue to return to get service from time to time because good service can provide satisfaction to patients following their needs and desires. This study aims to determine the effect of the quality of hospital administration services on patient satisfaction in the outpatient installation unit of Arifin Achmad Hospital, Riau Province. This type of research is quantitative by using a questionnaire. Respondents in this study were patients who had received outpatient registration services at Arifin Achmad Hospital, Riau Province. The results of the study obtained a total of 100 respondents. The analysis results show that all service quality indicators (Tangible, Reliability, Responsiveness, Assurance, Empathy) positively influence the service quality of hospital administrative staff on patient satisfaction in the outpatient installation unit of Arifin Achmad Hospital, Riau Province. There are two service quality indicator variables that have the most dominant influence on patient satisfaction in the outpatient installation unit of the Arifin Achmad Hospital, Riau Province, which include the Assurance indicator 48.6% and Tangible 24.3% and show that 63.6% of the patient satisfaction variable can be explained. by the service quality of hospital administrative staff, so it can be concluded that the service quality of hospital administrative staff in outpatient installations greatly influences patient satisfaction.